THE WEB OF SYSTEM PERFORMANCE. - Whitworth, Brian; Fjermestad, Jerry; Mahinda, Edward (Communications of the ACM, 2006)
The article focuses on specialist theories of performance dimensions in information system performance. According to the author, modern information systems face demands so diverse that some computer science researchers theorize that a virtual evolution exists, where only the fittest applications survive. The eight performance goals of WOSP (web of system performance) are discussed. It is the author's view that as information systems become more critical, performance-integration issues will become more critical.